2015
DOI: 10.1021/acsnano.5b02374
|View full text |Cite
|
Sign up to set email alerts
|

Clotting Mimicry from Robust Hemostatic Bandages Based on Self-Assembling Peptides

Abstract: Uncontrolled bleeding from traumatic wounds is a major factor in deaths resulting from military conflict, accidents, disasters and crime. Self-assembling peptide nanofibers have shown superior hemostatic activity, and herein, we elucidate their mechanism by visualizing the formation of nanofiber-based clots that aggregate blood components with a similar morphology to fibrin-based clots. Furthermore, to enhance its direct application to a wound, we developed layer-by-layer assembled thin film coatings onto comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
90
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(92 citation statements)
references
References 43 publications
0
90
0
Order By: Relevance
“…For example, Kumar et al reported that snake venom laded self‐assembling nanofibrous peptide hydrogel is a facile method for surgical hemostasis . Similarly, Hsu et al showed that self‐assembling peptides, especially RADA16‐I, are highly effective in generating in hemostasis with a hemostasis time of <10 s . In their study, an antibiotic released self‐assembled film developed for rapid hemostat .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kumar et al reported that snake venom laded self‐assembling nanofibrous peptide hydrogel is a facile method for surgical hemostasis . Similarly, Hsu et al showed that self‐assembling peptides, especially RADA16‐I, are highly effective in generating in hemostasis with a hemostasis time of <10 s . In their study, an antibiotic released self‐assembled film developed for rapid hemostat .…”
Section: Introductionmentioning
confidence: 99%
“…The self-assembling peptides have ability to coagulate blood by forming nanofiber to entrap blood corpuscles 14 . We examined the formation of blood clot by designed sealants using scanning electron microscopy (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ideally, such nature-inspired sealants should be biocompatible and biodegradable with minimal inflammatory response 5–13 . The natural process of blood clotting involves entrapment of blood corpuscles and platelets by fibrin 14, 15 . Fibrin is formed due to thrombin mediated polymerization and factor XIIIa induced intermolecular isopeptide bond mediated cross-linking of fibrinogen 4, 1621 .…”
Section: Introductionmentioning
confidence: 99%
“…By sequentially immersing substrates in polymer solutions with complimentary intermolecular interactions (e.g., electrostatic, hydrogen, covalent, etc. ), one can generate robust thin films composed of a broad set of materials like inorganics, micro‐to‐nanoparticles, biologics, peptide nanofibers, and small molecules . These films can have diverse applications, which have been well reviewed .…”
Section: Introductionmentioning
confidence: 99%
“…While there are a number of reports showing the viability of Spray‐LbL with polypeptides and polysaccharides, there remains a dearth of Spray‐LbL assembled controlled drug release systems. The limited examples include release of vancomycin, thrombin, self‐assembled peptides, and dexamethasone, which have shown the promise of this technique. Herein, we describe improvements to the current Spray‐LbL approach of film assembly by designing individual containment chambers for each aerosolized solution, which allows them to be separately collected and analyzed or returned to their original reservoir (i.e., recycling the solution).…”
Section: Introductionmentioning
confidence: 99%